2021
DOI: 10.1136/bmjgh-2020-004836
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of paediatric latent tuberculosis infection care cascades: initial steps are lacking

Abstract: Background and objectivesIdentifying and treating children with latent tuberculosis infection (TB infection) is critical to prevent progression to TB disease and to eliminate TB globally. Diagnosis and treatment of TB infection requires completion of a sequence of steps, collectively termed the TB infection care cascade. There has been no systematic attempt to comprehensively summarise literature on the paediatric TB infection care cascade.MethodsWe performed a scoping review of the paediatric TB infection car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…Despite supportive evidence and existing WHO and national-level recommendations for CCM, many barriers still exist to their implementation. Recent systematic reviews have identified key challenges for CCM implementation and delivery of TPT, which include knowledge, attitudes, fear of stigma, poor access to tuberculin skin test (TST) and interferon gamma release assay (IGRA) for TB infection identification, poor access to chest radiography (CXR) to rule out active TB disease before TPT initiation, competing priorities for parents, and long treatment regimens affecting treatment adherence [10][11][12]. The impact of interventions deployed to overcome some of these challenges was summarized in an additional systematic review [13].…”
Section: National Policies and The Policy-practice Gapmentioning
confidence: 99%
“…Despite supportive evidence and existing WHO and national-level recommendations for CCM, many barriers still exist to their implementation. Recent systematic reviews have identified key challenges for CCM implementation and delivery of TPT, which include knowledge, attitudes, fear of stigma, poor access to tuberculin skin test (TST) and interferon gamma release assay (IGRA) for TB infection identification, poor access to chest radiography (CXR) to rule out active TB disease before TPT initiation, competing priorities for parents, and long treatment regimens affecting treatment adherence [10][11][12]. The impact of interventions deployed to overcome some of these challenges was summarized in an additional systematic review [13].…”
Section: National Policies and The Policy-practice Gapmentioning
confidence: 99%
“…When evaluating why do children not complete TPT, a scoping review of 146 studies identified concerns about adverse effects, low income, stigma, and transport as barriers and found these factors to be associated with lower retention in care [ 16 ]. Conversely, caregiver education and shorter regimens facilitated the completion of TPT [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When evaluating why do children not complete TPT, a scoping review of 146 studies identified concerns about adverse effects, low income, stigma, and transport as barriers and found these factors to be associated with lower retention in care [ 16 ]. Conversely, caregiver education and shorter regimens facilitated the completion of TPT [ 16 ]. Health system aspects such as poor linkage to TB services, patient’s mistrust of the health system, and lack of commitment to shared responsibility on TPT adherence by providers impacted treatment initiation, adherence, and completion in both adults and children on TPT [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review from Campbell et al highlighted the fact that a well-defined cascade of care is not being followed for systematic evaluation of pediatric latent TB infection. Most of the studies have focused on the aspect of treatment initiation and completion, while the other components such as screening, investigation, and not initiating TB preventive treatment are given lesser importance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%